A systematic analysis of the global, regional, and national burden of fungal skin diseases from 1990 to 2021 - Wang, Hongping; Sun, Fengjun; Wang, Changquan; Ye, Jin; Xia, Peiyuan; Wang, Wanneng; Wu, Yaguang (Frontiers in Epidemiology, 2024)
We aimed to assess the burden of Fungal Skin Diseases (FSD) in 2021 and explore the changing trends from 1990 to 2021 across different age groups and time periods.Methods: This study extracted three key indicators of the burden of FSD from the Global Burden of Disease (GBD) 2021 study: prevalence, incidence, and disability-adjusted life years (DALYs). The results were presented using point estimates and Uncertainty Intervals (UIs), and secondary analysis was conducted on these data to assess the changing trends in the burden of FSD using percentage change.